Intensity modulated radiotherapy in the management of sacral chordoma in primary versus recurrent disease - Zabel-du Bois, Angelika; Nikoghosyan, Anna; Schwahofer, Andrea; Huber, Peter E.; Schlegel, Wolfgang; Debus, Jürgen; Milker-Zabel, Stefanie (Radiotherapy and oncology, 2010)
Purpose - To investigate treatment outcome in patients suffering from sacral chordoma after intensity modulated radiotherapy (IMRT) for primary versus recurrent disease. - Material/methods - We report on 34 patients with histologically proven sacral chordoma. Seventeen patients were treated at time of initial diagnosis with post-operative IMRT (n=13) or with IMRT alone (n=4). Seventeen patients were treated in recurrent disease after surgery (n=11) or with radiotherapy alone (n=6). Median total dose to the boost volume (PTV2) was 66Gy (range, 72-54) with 2Gy per fraction using an integrated boost concept. Median dose to target volume (PTV1) was 54Gy in 1.8Gy. - Results - Local control was 35% (12/34) and overall survival 74% (25/34) after a median follow-up of 4.5years. Actuarial local control was 79%, 55% and 27% after 1, 2 and 5years, respectively. Local control was significantly higher in patients treated for primary tumors (p<0.03) and in total doses >60Gy (p<0.01). Actuarial overall survival was 97%, 91% and 70% after 1, 2 and 5years, respectively. - Conclusion - These data demonstrate that local control after IMRT is higher in patients treated for primary tumors and using higher radiation doses. Therefore, we recommend radiotherapy as part of initial treatment in sacral chordoma.